2004
DOI: 10.1017/s095026880300178x
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of an avian pox outbreak in wild red-legged partridges (Alectoris rufa) in Spain

Abstract: This study describes the dynamics and epidemiology of an outbreak of avian pox in free-living, red-legged partridges (Alectoris rufa) in southern Spain. Between March 2000 and January 2001, 115 free-living, red-legged partridges (70 juveniles, 45 adults) were captured and radio-tagged. This, together with the necropsy of 44 carcasses (10 juveniles, 34 adults) found in the study area, and the inspection of 108 shot birds (74 juveniles, 34 adults) after a hunting drive in October, permitted a close monitoring of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 13 publications
3
19
4
Order By: Relevance
“…In contrast to results from other studies on wild birds (Buenestado et al 2004;Atkinson et al 2005), our investigation found that the likelihood of being infected with avian pox or malaria did not differ in relation to either sex or age. Specifically, our results contrast with those of Smits et al (2005), whose findings indicate that in Fuerteventura and Lanzarote adult Berthelot's pipits had a higher prevalence of avian pox than juveniles.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to results from other studies on wild birds (Buenestado et al 2004;Atkinson et al 2005), our investigation found that the likelihood of being infected with avian pox or malaria did not differ in relation to either sex or age. Specifically, our results contrast with those of Smits et al (2005), whose findings indicate that in Fuerteventura and Lanzarote adult Berthelot's pipits had a higher prevalence of avian pox than juveniles.…”
Section: Discussioncontrasting
confidence: 99%
“…Viral diseases of birds that are shared between domestic flocks and wild birds can affect economically relevant game birds (e.g. avian pox and red-legged partridge, Buenestado et al 2004), or endangered birds, often boosting vaccination of captive individuals (e.g. West Nile encephalitis, SiegalWillott et al 2006).…”
Section: Diseases Affecting Wildlife Management and Conservationmentioning
confidence: 99%
“…These interfering factors can interact with each other as suggested for predation, diseases and artificial feeding (e.g. Packer et al 2003;Buenestado et al 2004;Millán et al 2004a). Hence, overabundance tends to be mostly a problem of ungulates in temperate, non-extreme climates with intense artificial management.…”
Section: Managing Overabundancementioning
confidence: 99%